An Inquiry into Juan Ramon's Interest in Walter Pater - John C. Wilcox (Studies in 20th & 21st Century Literature, 1983)
The evidence for Juan Ramon's interest in Pater, which began around 1920 and was still active twenty years later, is discussed in this paper. Pater's view of death and dying and his attitude toward the decadent persona are described in so far as they indicate the spiritual affinity that exists between him and Juan Ramón. Pater's aesthetic idealism, and the presence of similar ideals in Juan Ramon's own work are then examined. The second part of the paper concentrates on the great interest Juan Ramón took in Pater's evocation of the Mona Lisa. The potential impact of the aesthetic idealism inherent in this passage, its Platonism in particular, receives special analysis in the light of Espacio, and in consideration of Juan Ramon's 1943 remark: "I am, have been, and always will be a Platonist."
Keywords: Juan Ramón Jiménez; Walter Pater; English literature; Spanish poetry; death; dying; decadent persona; spiritual; aesthetic idealism; Mona Lisa; Platonism; Espacio